Optimizing treatment in recurrent epithelial ovarian cancer. Issue 12 (2nd December 2017) - Corrado, Giacomo; Salutari, Vanda; Palluzzi, Eleonora; Distefano, Maria Grazia; Scambia, Giovanni; Ferrandina, Gabriella
ABSTRACT: Introduction : Optimal management of recurrent ovarian cancer (ROC) remains an area of uncertainty. An estimated 85% of patients with epithelial ovarian cancer who achieve a full remission following first-line therapy will develop recurrent disease and median survival for these patients' ranges from 12 months to 24 months. Many patients receive several lines of treatment following recurrence and, although each subsequent line of therapy is characterized by shorter disease-free intervals, decisions about the most appropriate treatment is complex. Areas covered : This review focuses on chemotherapy, surgery and emerging biologic agents that present a therapeutic option for patients with ROC. Expert commentary : Recurrent ovarian cancer is not curable. The goals of therapy should focus on palliation of cancer-related symptoms, extension of life, and maintenance of quality of life. Patients with platinum-sensitive ovarian cancer should have their recurrence treated with a platinum-based agent. For patients whose cancer progresses after platinum retreatment and for those with platinum-resistant disease, numerous other non-platinum combination and targeted therapies have been shown to be effective in palliating cancer-related symptoms and extending life.